Lingue, letterature e culture migranti - Saracgil, Ayse; VEZZOSI, Letizia (Strumenti per la didattica e la ricerca, 2016)
The volume collects the contributions presented at the first Seminar organized in 2014 in Florence by the Section of Intercultural Studies of the Department of Languages, Literatures and Intercultural Studies on the theme "Languages, Literatures and Migrant Cultures". The essays - written by authors from the area of German studies and Germanic philology, Lusitanistics, Hispano-American studies, Sinology and Comparative studies - analyse various aspects of the theme of "migration" in the variety of its expressions: alongside strictly linguistic observations, they investigate the phenomenon of intercultural contact on a social, historical, literary and anthropological level.